2020
DOI: 10.1200/jco.2020.38.4_suppl.380
|View full text |Cite
|
Sign up to set email alerts
|

Palliative systemic chemotherapy with or without pressurized intraperitoneal aerosol chemotherapy with cisplatin and doxorubicin (PIPAC C/D) for gastric cancer with peritoneal metastasis: A propensity score analysis.

Abstract: 380 Background: Gastric cancer (GC) with peritoneal metastasis (PM) has a dismal prognosis. Palliative systemic chemotherapy (SC), usually doublet combinations of platinum and fluoropyrimidines, is the standard of care. Pressurized IntraPeritoneal Aerosol Chemotherapy with Cisplatin and Doxorubicin (PIPAC C/D) yields promising results. Here we aimed to compare overall survival (OS) between SC + PIPAC C/D vs. SC alone in patients with PM from GC. Methods: Prospective cohort of 95 consecutive patients with PM f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the final results, the estimated median survival was 49 months for the intraperitoneal cisplatin group and 41 months for the intravenous cisplatin group, and the risk of death was lower 131 In recent years, Khomiakov et al also compared the median overall survival of patients who received systemic chemotherapy plus PIPAC versus systemic chemotherapy alone in a propensity score analysis. 132 Not surprisingly, they came to similar conclusions as other previous studies, with median overall survival of 14.0 months in the group receiving systemic chemotherapy plus PIPAC and 7.0 months in the group receiving systemic chemotherapy alone. All of these clinical trials suggest that combination therapy is more effective and promising.…”
Section: Combined Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In the final results, the estimated median survival was 49 months for the intraperitoneal cisplatin group and 41 months for the intravenous cisplatin group, and the risk of death was lower 131 In recent years, Khomiakov et al also compared the median overall survival of patients who received systemic chemotherapy plus PIPAC versus systemic chemotherapy alone in a propensity score analysis. 132 Not surprisingly, they came to similar conclusions as other previous studies, with median overall survival of 14.0 months in the group receiving systemic chemotherapy plus PIPAC and 7.0 months in the group receiving systemic chemotherapy alone. All of these clinical trials suggest that combination therapy is more effective and promising.…”
Section: Combined Treatmentmentioning
confidence: 99%
“…In 2018, Shinkai et al evaluated the safety and efficacy of intraperitoneal PTX in combination with intravenous PTX, cisplatin, and S-1 in the treatment of patients with peritoneal metastatic cancer in a prospective phase II study, and post-treatment results showed that patients had a 1-year survival rate of approximately 80%, a median survival time of 18–25 months, and minimal complications . In recent years, Khomiakov et al also compared the median overall survival of patients who received systemic chemotherapy plus PIPAC versus systemic chemotherapy alone in a propensity score analysis . Not surprisingly, they came to similar conclusions as other previous studies, with median overall survival of 14.0 months in the group receiving systemic chemotherapy plus PIPAC and 7.0 months in the group receiving systemic chemotherapy alone.…”
Section: Clinical Treatment Options For Peritoneal Metastatic Cancermentioning
confidence: 99%